Analytic solutions for Hamilton-Jacobi-Bellman equations - Arsen Palestini (Electronic Journal of Differential Equations, 2017)
Closed form solutions are found for a particular class of Hamilton-Jacobi-Bellman equations emerging from a differential game among firms competing over quantities in a simultaneous oligopoly framework. After the derivation of the solutions, a microeconomic example in a non-standard market is presented where feedback equilibrium is calculated with the help of one of the previous formulas.